80.1k views
0 votes
Solve using substituion -5x + y = -2 -3x + 6y = -12

1 Answer

3 votes

Answer:

x = 0

y = - 2

Explanation:

-5x + y = -2………… Equation 1

-3x + 6y = -12 ………… Equation 2

Using substitution

Make y the subject in equation 1 and substitute it into equation 2 and solve for x

That's

y = 5x - 2

We have

- 3x + 6( 5x - 2) = - 12

- 3x + 30x - 12 = - 12

27x = - 12 + 12

27x = 0

Divide both sides by 27

x = 0

Substitute x = 0 into y = 5x - 2

We have

y = 5(0) - 2

y = - 2

So the solutions are

x = 0

y = - 2

Hope this helps you

User CmdrSharp
by
4.8k points